The function of macroprudential policy on loan growth and risk-taking in Islamic Banking and Financial Institutions: evidence from Islamic countries - Habibullah, Mohammad; Md, Atiullah (IIUM Institute of Islamic Banking and Finance (IIiBF), 2022)
Abstract The recent Global Financial Crisis (GFC) has emphasized the importance of the implementation of Macroprudential Policy (MPP) to promote financial stability in the banking and financial institutions. The main objective of this paper is to evaluate loan growth and bank risk-taking tendency by Islamic banks during crisis and normal periods and how MPP moderate the relationship between loan growth and risk-taking to promote financial stability in the Islamic financial institutions. This paper will use a dynamic panel dataset to regress the analysis from the year 2005-2020. The paper will apply Z-score to measure bank risk and the Generalized Method of Moments (GMM) will be used to measure the impact of MPP on the relationship between loan growth and bank risk-taking. However, the empirical findings will suggest which particular MPP are more suitable and effective in controlling abnormal loan growth and risk-taking appetite to enhance financial stability in the Islamic banking and financial institutions. Though, Islamic banking and financial institutions are still in the infancy stage of implementing macroprudential policy, hence, it is important to investigate how macroprudential tools are effective in Islamic financial institutions as compared to conventional financial system.